Optimization of biodiesel production over alkaline modified clay catalyst - Ayoub, M. (Japan Institute of Energy, 2017)
The demand for energy and its resources is increasing daily due to the rapid outgrowth of population and urbanisation. Petroleum is a non-regenerate source of energy. The increasing price of petroleum and environment concerns making the search for alternative renewable fuels is gaining considerable attention. Biodiesel is among the most promising alternative fuel to replace petroleum-based diesel. In this work, biodiesel was produced via transesterification of palm oil with methanol in the presence of heterogeneous catalyst alkaline based clay KOH/MK-10. The surface and structural properties were measured via latest techniques of SEM and BET surface analysis. The characterisation of prepared catalyst showed that surface area and pore volume of modified clay decreased but the morphology of clay was observed as the same after potassium modification. The results showed that prepared KOH/MK-10 is highly active for transesterification reaction under optimized condition. The maximum conversion of triglyceride was noted 98 after 3 h of reaction at 60°C with a 15:1 molar ratio of methanol to palm oil and 3 wt of the prepared catalyst.